Analisis Kelayakan Usaha Peternakan Ayam Kampung Di Desa Rondaman Jae Kecamatan Halongonan Timur Kabupaten Padang Lawas Utara - Ulina Hutasuhut; Ari Andani Nasution (Indonesian Journal of Innovation Science and Knowledge, 2026)
Operating a livestock business with a substantial herd size requires sound, professional planning and management—particularly regarding initial capital, daily operating costs, husbandry practices, product marketing, and accurate revenue and profit calculations. Challenges faced by small-to-medium-scale farmers include fluctuating feed prices (which account for 60–70% of total production costs), working capital availability, limited market access, and a lack of knowledge regarding business feasibility analysis. This study employs a quantitative descriptive method to provide a comprehensive overview of production cost components, revenue levels, and profitability in a household-scale free-range chicken farming business. Purposive sampling—a method of deliberately selecting a sample based on specific criteria established by the researcher—was utilized. The study relies on both primary and secondary data. The findings indicate that the "Ternak Ceria" free-range chicken business is viable for operation and expansion based on the following: (1) an R/C Ratio of 1.50, indicating efficient cost utilization; (2) a B/C Ratio of 0.50, indicating a profitable return; (3) a Unit Break-Even Point (BEP) of 67 birds—lower than the actual production capacity of 100 birds—providing a 33% margin of safety; (4) a Price BEP of Rp33,300, which is well below the actual selling price (Rp50,000), offering a high price margin of safety; and (5) a Margin of Safety of 33%, demonstrating the business's resilience against market fluctuations and sales declines.